The Big Wave - Buck, Pearl S. (New York Scholastic Inc., 1948)
His family and village swept away by a tidal wave, Jiya learns to live with the ever-present dangers from the sea and volcano.
G5
Keywords: Japan -- Juvenile fiction; Ocean waves -- Juvenile fiction; Tsunamis -- Juvenile fiction